Utilization of Closed Circuit Television in Improving Nurse's Compliance on Hand Hygiene in Budhi Asih Hospital Jakarta - Ramadhanti, Ahijrah; Dwiprahasto, Iwan; Nirwati, Hera (Jurnal Keperawatan Soedirman, 2020)
Health-care associated infections (HAIs) are infectionsoccurring inhospitalized patients.The most effective way to prevent HAIsis throughhand hygiene. However, hand hygiene compliance in health workers is still low. This research aimed to understandtheassociation between CCTVutilizationas a reminder tool inimproving the nurses'hand hygiene compliancein Budhi AsihHospitalJakarta. The study used a quantitativemethod bya quasi-experimentalapproach. The 60 subjects weredivided into two groups:Treatment and Control Groups based on their workplace. Quantitative data wereobtained by filling-in a WHO-standardized questionnaire and observing each group before and after an intervention. Data were analyzed by univariate and bivariate analyses with chi-square test and multivariate analysis with logisticregression test. Nurses' hand hygiene compliance through CCTV observation in Budhi Asih Hospital was 57%. The use of CCTV as reminder media significantly improved hand hygiene compliance (p = 0.002), compliance to 6 steps (p = 0.002) and compliance to the standard time of hand hygiene (p = 0.003). There was no significant correlation between individual characteristics (sex, age, education, working experience, and infection control training participation) with nurses' compliance on hand hygiene. The use of CCTV as reminder media significantly improved nurses' compliance to do hand hygiene.Keywords: CCTV, Reminder, Hand Hygiene, Complience.